Title Risk Identification Techniques in Valuation and Investment Appraisal - Danazimi Jibril, Jibril; Toyin J, Zainab; ., . (International Journal of Engineering and Technology, 2018)
This study investigated the risk analysis in property valuation and investment appraisals in Nigerian estate firms, this was carried out through the risk identification techniques. Risk and uncertainty are the inherent part of the valuation and appraisal process. Self-administered questionnaire was employed using likert scaling to collect the data from 95 estate surveying and valuation firms, while the data was analyzed using descriptive statistic. The study revealed that the most peculiar risk to real estate valuation and investments is legal risk base on the ranking. Investment appraisal reports however indicated that sensitivity analysis is the most used technique. In view of the above, the certainty equivalent and Monte Carlos stimulation was recommended if all things are equal in respect of availability of data and a stable economic situation. The study identified legal risk is the major risk found in valuation and investment appraisal, thus the result indicated that, Surveyors in the study area have very little knowledge of risk and uncertainty as revealed in their reports. Finally it was recommended that, a lot need to be done on the level of awareness and understanding valuers toward incorporating risk and uncertainty in property valuation and investment appraisal. Â